Hypoglycemic Effect of a Combined Andrographis paniculata and Caesalpinia sappan Extract in Streptozocin-Induced Diabetic Rats - Febrika Wediasari; Gumilar A. Nugroho; Zahra Fadhilah; Berna Elya; Heri Setiawan; Tjandrawati Mozef (Hindawi Limited, 2020)
Introduction. Researchers usually use herbal combinations to explore and develop traditional medicine to obtain additional benefits in the treatment of diseases, including diabetes. This study aims to evaluate the hypoglycemic effect of the combination of Andrographis paniculata (Burm. f.) Wall ex Nees and Caesalpinia sappan Linn extract (APCSE) on diabetes-induced rats. There has not been sufficient research on this combination; however, single extract studies of these plants have been widely conducted. Materials and Methods. Male Sprague Dawley rats (160-200 g) were induced by injecting a low dose of streptozotocin (35 mg/kg BW) twice and fed with a high-fat diet containing 25% fat, whereas control animals received only standard feed. Rats were treated with APCSE at doses of 100 mg and 200 mg/kg BW for seven days and compared to the APE and CSE groups treated with the extract at 100 mg, respectively. For the control group, rats were treated with metformin with a dose of 250 mg/kg. The antihyperglycemic and antihyperlipidemic effects were determined by measuring blood glucose levels and lipid profiles (cholesterol, triglycerides, HDL, and LDL). To assess the impact of the extract on pancreatic and adipose tissue, the number of pancreatic beta cells and adipocytes was evaluated through histopathological and immunohistochemical study. Results and Discussion. In a nonfasting state, the blood glucose change in APCSE 200 mg was 18.65% and was significantly lower from the DM group. However, a single extract of APE and CSE showed lower fasting blood glucose levels compared to the combined extract. Lipid profiles show no significant differences in cholesterol levels between groups; however, all treatment groups, including metformin, showed higher triglyceride levels. The APE-treated group showed significantly lower HDL and LDL, whereas CSE only showed lower LDL. The β-cell number was significantly higher after treatment with single extract CSE. The CSE and the combined extract groups showed hyperplasia adipocytes. Conclusion. The combined extract of APCSE has a moderate antihyperglycemic effect; however, a single extract may have better potential than the combined extract.